Mendiskusikan Penelitian-penelitian Terdahulu dengan Tema â€œPolitik Uang di Indonesiaâ€ dari Tahun 1983-2023 Berdasarkan Pencarian Scopus - Aprillia, Bunga; Yamardi, Yamardi (Sawala : Jurnal Administrasi Negara, 2023)
Money politics in Indonesia is a phenomenon that often occurs in general elections at the central, regional and village levels. There are very few studies on money politics in the world, in a Scopus search from 1983-2023 there were only 50 documents discussing it. Among the 50 writers, there are dominated by writers from Indonesia who study money politics in Indonesia. This research is descriptive research using the literature study method. The literature study method is a series of activities related to methods of collecting library data, reading, and taking notes, and managing research materials. Based on Scopus search results, of the 50 documents only 7 (seven) documents are relevant to Indonesia's political conditions. This previous research document discusses the origins of money politics from the new order to money politics from a gender dan religiosity perspective. The results of the research state that money politics is about people's willingness to buy votes but normatively it does not determine the choice of political party that gives monetary gifts. Keywords: Literature Study, Money politic, Scopus website.